Evaluating the Effectiveness of the Poor Student Assistance Program (PSAP) in Improving Academic Achievement Among Low-Income Elementary School Students - Rey Acher Zaki; Christabel Maellisa (Jurnal Ilmu Pendidikan dan Humaniora, 2024)
This research evaluates the effectiveness of the Poor Student Assistance Program (PSAP) in enhancing academic achievement among elementary school students from low-income backgrounds. The study investigates the primary factors influencing academic achievement and examines the correlation between PSAP participation and improvements in student outcomes. Utilizing a mixed-methods approach, including surveys, standardized test scores, and qualitative interviews, the research identifies socio-economic status, quality of instruction, family support, school climate, and student engagement as key determinants of academic success. The findings reveal a significant positive correlation between PSAP participation and academic performance, with participants demonstrating higher gains in standardized test scores, grades, and attendance rates compared to non-participants. These results underscore the effectiveness of targeted interventions like the PSAP in addressing educational disparities and promoting equitable outcomes for all students. The implications derived from the study's findings highlight the importance of targeted interventions, resource allocation, evidence-based practices, holistic support, differentiated instruction, family engagement, and a focus on long-term impact and contextual factors. Ultimately, this research contributes to the broader discourse on educational equity and offers actionable insights for policymakers, educators, and researchers seeking to promote academic success among economically disadvantaged students.